Analisis pengaruh kebijakan deviden, resiko bisnis, kontrol kepemilikan, cash holding dan non debt tax shield terhadap struktur modal pada perusahaan manufaktur yang terdaftar di bursa efek Indonesia - Rizky Ardhianto; Emrinaldi Nur Dp; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Capital structure relates to how companies finance their debts and make decisions about the shape and composition of funding that will be used by the company. Financing companies can be debt or equity capital and need to be considered when obtaining these funds. Several factors can affect the capital structure is the dividend policy, business risk, ownership control, cash holding and non-debt tax shield. This study aims to determine the effect of dividend policy, business risk, ownership control, cash holding and non-debt tax shield on capital structure in companies listed in Indonesia Stock Exchange.The results of this study found that the Dividend Policy, Business Risk, Ownership Control and Cash Holding has a significant effect on capital structure. While Non-Debt Tax Shields did not have a significant effect on capital structure. The results of this study also found that the dividend policy, business risk, ownership control, Cash Holdings, and non-debt tax shield together have an influence on the capital structure. The influence of independent variables on the dependent variable capital structure which can be described by the equation by 40.1%. While 59.9% influenced by other factors not included in the regression model.Keywords : Dividen Policy, Business Risk, Ownership Control, Cash Holding, Non Debt Tax Shield, and Capital Structure